Arthritis-related work outcomes experienced by younger to middle-Aged adults: A systematic review - Berkovic, D.; Briggs, Andrew; Ayton, D.; Parker, C.; Ackerman, I. (BMJ PUBLISHING GROUP, 2021)
Objective The aim of this review was to systematically identify, appraise and synthesise evidence on work-related outcomes experienced by younger to middle-Aged adults (aged 16-50 years) with arthritis. Methods Eligible studies were identified in Medline, PsycINFO, Embase and CINAHL in January 2020. Quantitative and qualitative studies containing self-reported data on work-related outcomes on younger/middle-Aged adults with arthritis were included. Quality assessment was undertaken using validated quality appraisal tools from the Joanna Briggs Institute. Results Thirty-four studies were identified for inclusion. Work outcomes were organised around five themes: (1) arthritis-related work productivity outcomes, (2) arthritis-related work participation outcomes, (3) other arthritis-related workplace outcomes, (4) barriers to work participation associated with arthritis and (5) enablers to work participation associated with arthritis. Arthritis was associated with work limitations on the Workplace Activity Limitations Scale (average scores ranging from 5.9 (indicating moderate workplace difficulty) to 9.8 (considerable workplace difficulty)), and higher work disability prevalence rates (range: 6%-80%) relative to healthy populations. Arthritis was not associated with decreased absenteeism on the Work Productivity and Activity Impairment Questionnaire (mean (SD) 7.9% (14.0%)), indicating low levels of absenteeism, similar to healthy populations. As work outcomes were commonly binary, person-centred (qualitative) perspectives on barriers and enablers augmented the quantitative findings. Conclusion Arthritis is commonly associated with poorer work outcomes for younger/middle-Aged adults relative to healthy populations. Additional research focusing solely on the workplace needs of younger/middle-Aged population groups is required to inform tailored interventions and workplace support initiatives to maximise productive working years.